Increased Pneumonia-Related Emergency Department Visits, Northern Italy - Villa, Simone; Maffeo, Manuel; Maistrello, Mauro; Bagarella, Giorgio; Porrello, Vincenzo Navobi; Morani, Federica; Scovenna, Francesco; Baldanti, Fausto; Bonfanti, Paolo; Pariani, Elena; Gori, Andrea; Vezzosi, Luigi; et al. (Emerging infectious diseases, 2025)
An increase in pneumonia-related emergency department visits was observed in Lombardy, northern Italy, during June-October 2024. Viral causes appear insufficient to explain the increase, suggesting a bacterial cause. Mycoplasma pneumoniae and Bordetella pertussis emerged as possible causes when other surveillance systems were consulted, but the reasons behind this trend remain unknown.